Review of Neurosurgical services at B&C Hospital in last 3 years - Thapa, Dinesh K. (Eastern Green Neurosurgery, 2019)
Neurosurgery was started in Far-Eastern Nepal as Department of Neurosurgery at B&C Hospital in early 2015. Prof.Dr. Basant Pant played a key role to establish and give astounding start with all technical supports possible. Dr. Chandra P Limbu and I joined the institute at the beginning from ANIAS. Since last one year the department is led by Dr. Pankaj Raj Nepal, who is one of the finest trainee of Prof. Upendra P. Devkota. The set up of the operating theatre is allowing us to do almost all types of neurosurgical procedures. In last three years there were 336 head injuries cases among which acute subdural hematoma was the commonest one. There were 48 cases of cervical spine injuries cases admitted over this duration. Hemorrhagic stroke requiring surgical procedure were 46 followed by 11 cases of malignant MCA infarction. Tumors were of different types and were 83 cases during this period. Aneurysms were 46 in number who underwent clipping.